The volatility of capital flows in emerging markets measures and determinants - Maria Sole Pagliari; Swarnali Ahmed Hannan (Rutgers University, Department of Economics, 2017)
Capital flow volatility is a concern for macroeconomic and financial stability. Nonetheless, literature is scarce in this topic. Our paper sheds light on this issue in two dimensions. First, using quarterly data for 33 emerging markets and developing economies over the period 1970Q1-2016Q4, we construct three measures of volatility, for total capital flows and key instruments. Second, we perform panel regressions to understand the determinants of volatility. The measures show that, after a period of sharp rise during the Global Financial Crisis, the volatility of most instruments is back to pre-crisis levels but are prone to bouts, having increased significantly during global shocks like the taper tantrum episode. Capital flow volatility thus remains a challenge for policy makers. The regression results suggest that push (external) factors are generally more important than pull (domestic) factors in explaining the volatility of capital flows. However, certain pull factors have become relevant since the Global Financial Crisis.
Keywords: C13; C33; C58; F32; F36; F40; 330; Volatility Estimation; International Flows; Push vs Pull Factors